(19b-6)-6(3b+3)=-7

Simple and best practice solution for (19b-6)-6(3b+3)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (19b-6)-6(3b+3)=-7 equation:


Simplifying
(19b + -6) + -6(3b + 3) = -7

Reorder the terms:
(-6 + 19b) + -6(3b + 3) = -7

Remove parenthesis around (-6 + 19b)
-6 + 19b + -6(3b + 3) = -7

Reorder the terms:
-6 + 19b + -6(3 + 3b) = -7
-6 + 19b + (3 * -6 + 3b * -6) = -7
-6 + 19b + (-18 + -18b) = -7

Reorder the terms:
-6 + -18 + 19b + -18b = -7

Combine like terms: -6 + -18 = -24
-24 + 19b + -18b = -7

Combine like terms: 19b + -18b = 1b
-24 + 1b = -7

Solving
-24 + 1b = -7

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 1b = -7 + 24

Combine like terms: -24 + 24 = 0
0 + 1b = -7 + 24
1b = -7 + 24

Combine like terms: -7 + 24 = 17
1b = 17

Divide each side by '1'.
b = 17

Simplifying
b = 17

See similar equations:

| msquared+9m=0 | | x-5/3=7 | | 4(2a-1)=-10a(a-5) | | 2x^3-10x^2=8x | | h(0)=-16t^2(1)+15(1)+12 | | 4*(x-9)=20 | | 51/5+x=8 | | -4(-2t+1)=-(-4+10t) | | 4*x-9=20 | | h(0)=-16t^2(1)+95(1)+0 | | 9x/x+3-2x-21/x+3 | | -6=y/7 | | x^30=x | | h(0)=-16t^2(1)+28(1)+5 | | -3(x+5)=4(x-1) | | -2p-4(2p+9)=6p-10 | | y^2-16y+63=0 | | h(0)=-16t^2(t)+28(t)+5 | | -4x-6y=-28 | | h(0)=-16t^2(0)+28(0)+5 | | 4+2*x=7+x | | -x+7=-16 | | 2/5p=32.7 | | 25-3(6-x)=7 | | 5x+3=-(x-21) | | 8-x*2=20+x | | 4x-2=7x-4x | | 8-x^2=20+x | | s-4=5 | | 2/3-5/4=-1/5y+4/3y | | 2x+1=5x-4 | | 3+4(x-3)=-13 |

Equations solver categories